Determinants of Shopee Customer Satisfaction: Price, Product Quality, and Service Quality - Epferiyansah, Adit; Pentiana, Destia; Dewi, Anita Kusuma (Goodwood Akuntansi dan Auditing Reviu, 2026)
Purpose: This study aims to analyze the influence of price, product quality, and service quality on consumer satisfaction with Shopee among Accounting students at Politeknik Negeri Lampung. Methodology/approach: A quantitative approach was employed using a survey questionnaire distributed to 100 respondents. Data were analyzed using multiple linear regression, t-test, F-test, and coefficient of determination through IBM SPSS Statistics 26. Validity and reliability tests were conducted, and outliers were removed, resulting in 94 valid respondents. Results/findings: The results indicate that product quality (beta = 0.646, p-value = 0.000) and service quality (beta = 0.557, p-value = 0.000) have a significant positive effect on consumer satisfaction, while price (beta = 0.153, p-value = 0.239) does not show a significant influence. The regression model is significant simultaneously (F = 37.041, p-value = 0.000) with an adjusted R-squared of 0.538, indicating that 53.8 percent of the variance in consumer satisfaction is explained by the independent variables. Conclutions: Product quality and service quality are the primary drivers of consumer satisfaction in e-commerce platforms. Limitations: The sample is limited to one study program and institution, and the quantitative design limits in-depth exploration of subjective reasons. Contributions: This research provides empirical evidence on youth consumer behavior in digital marketplaces within a regional context in Sumatra, Indonesia, and supports the application of Expectation Confirmation Theory in e-commerce settings.